Efficacy and safety of non-pharmacological interventions for neonatal pain: an overview of systematic reviews - Xufei Luo; Qiao Shen; Zixuan Huang; Hongyao Leng; Xianlan Zheng (BMJ Open)
Objectives To synthesise current evidence from systematic reviews (SRs) regarding the efficacy and safety of non-pharmacological interventions to prevent and treat pain in newborn infants.Design Overview of SRs.Data sources We searched PubMed, Embase, Cochrane Library, Web of Science, CINAHL, Chinese National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), Wanfang Database, Chinese Science and Technology Periodical Database (VIP) and Google Scholar to identify all relevant SRs published in the last 5 years.Eligibility criteria for selecting studies We included SRs that evaluated the efficacy and safety of non-pharmacological interventions for neonatal pain.Data extraction and synthesis Two reviewers independently extracted the data, assessed the methodological quality using a Measurement Tool to Assess Systematic Reviews (AMSTAR) 2 and graded the evidence quality with the Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results A total of 29 SRs were included in this overview, of which 28 focused on procedural pain and only 1 focused on postoperative pain. Based on AMSTAR 2, seven reviews were found to be of ‘high quality‘, eight of ‘moderate quality’, five of ‘low quality’ and nine of ‘critically low quality’. The GRADE results suggested that facilitated tucking, kangaroo care, sweet solutions, familiar odour or combined non-pharmacological interventions, such as a combination of sucrose and non-nutritive sucking, were effective and safe in reducing pain from medical procedures in neonates. However, sucrose alone was less effective than local anaesthesia or a combination of the two during circumcision.Conclusions Facilitated tucking, small volumes of sweet solutions, kangaroo care and familiar odour were recommended. Scientific implementation strategies should be developed to promote the clinical use of these effective non-pharmacological interventions. Meanwhile, further rigorous trials and SRs are needed to identify the best non-pharmacological approaches for pain from common surgery and illnesses in neonates.PROSPERO registration number CRD42021292583.